2018
DOI: 10.1128/jb.00760-17
|View full text |Cite
|
Sign up to set email alerts
|

Two dd -Carboxypeptidases from Mycobacterium smegmatis Affect Cell Surface Properties through Regulation of Peptidoglycan Cross-Linking and Glycopeptidolipids

Abstract: During the peptidoglycan (PG) maturation of mycobacteria, the glycan strands are interlinked by both 3-3 (between two -diaminopimelic acids [-DAPs]) and 4-3 cross-links (between d-Ala and -DAP), though there is a predominance (60 to 80%) of 3-3 cross-links. The dd-carboxypeptidases (dd-CPases) act on pentapeptides to generate tetrapeptides that are used by ld-transpeptidases as substrates to form 3-3 cross-links. Therefore, dd-CPases play a crucial role in mycobacterial PG cross-link formation. However, the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Changes in PG cross-linking lead to alteration in curvature and helicity of Helicobacter pylori (Sycuro et al, 2010). Alteration in the ratio of tetra–tri and tri–tri cross-links also lead to changes in surface glycopeptidolipids, colony morphology, and biofilm formation in Mycobacterium smegmatis (Pandey et al, 2018). Growth medium-dependent glycine incorporation in PG is also observed in Caulobacter crescentus (Takacs et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in PG cross-linking lead to alteration in curvature and helicity of Helicobacter pylori (Sycuro et al, 2010). Alteration in the ratio of tetra–tri and tri–tri cross-links also lead to changes in surface glycopeptidolipids, colony morphology, and biofilm formation in Mycobacterium smegmatis (Pandey et al, 2018). Growth medium-dependent glycine incorporation in PG is also observed in Caulobacter crescentus (Takacs et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In mycobacteria, however, 80% of the crosslinks are the non-classical 3 → 3 linkage ( Kumar et al, 2012 , Lavollay et al, 2008 ). These cross-links are formed by the combined activities of the D,D-carboxypeptidases of the monofunctional PBPs, which remove the terminal D-Ala from one sidechain ( Pandey et al, 2018 ), followed by the activity of the L,D-transpeptidases (Ldts), which cleaves the next D-Ala and forms a 3 → 3 crosslink between two m -DAP residues of nearby sidechains ( Laponogov et al, 2009 ). There are two Ldts encoded in the Mtb genome, termed Ldt Mt1 (LdtA; Rv0116c) and Ldt Mt2 (LdtB; Rv2518c) ( Gupta et al, 2010 ), which are structurally unrelated to the PBPs and contain an active-site cysteine instead of serine ( Biarrotte-Sorin et al, 2006 , Mainardi et al, 2005 ).…”
Section: The Cell Wall Corementioning
confidence: 99%
“…PBP5 of E. coli helps the cells to recover from morphological deformities in septuple PBP mutant E. coli where L182 in its omega loop plays an imperative role in its activity [16,19]. A previous study from our laboratory showed that the deletion of MSMEG_2433 and MSMEG_2432 changed the cell shape and length along with the nature of PG cross-link formation in M. smegmatis [15]. The dual functionality (β-lactamases and dd-CPase) of MSMEG_2433 has also been reported whose activity is affected by E104A substitution (E75A in gene devoid of signal sequence) [10].…”
mentioning
confidence: 95%
“…dd-CPases catalyze the cleavage of terminal d-Ala 5 from the muramyl-pentapeptide (l-Ala 1 -d-iso-Glu 2 -meso-DAP 3 -d-Ala 4 -d-Ala 5 ) to generate tetrapeptides, the substrates of l-dtranspeptidases, which in turn is responsible for forming the 3-3 crosslinks between the adjacent peptides [14]. dd-CPases in mycobacteria are also responsible for preventing the unwanted crosslink formation (4-3 crosslinks in mycobacteria) as the deletion of dd-CPases shifts the 3-3 to 4-3 crosslink formation [15], though the dd-CPases are non-essential for bacterial survival [16]. Biochemically, dd-CPases contain SXXK, (S/Y)XN, and (K/H)(T/S)G motifs where Serine of SXXK plays a major role in the substrate binding [17,18].…”
mentioning
confidence: 99%